Lactation wise performance of Sahiwal cattle at an organized herd of northern India - RATWAN, POONAM; CHAKRAVARTY, A K; KUMAR, MANOJ (The Indian Journal of Animal Sciences, 2021)
Performances of different production, reproduction traits and longevity up to sixth parity in Sahiwal cattle maintained at ICAR-National Dairy Research Institute over a period of 29 years (1988–2016) were assessed. Parity wise means along with standard errors of different traits were estimated up to sixth parity in Sahiwal cattle using Descriptive Statistics in SPSS software. 305 days milk yield, total milk yield, lactation length, wet average, peak yield, days to attain peak yield and dry period varied from 1,822.59 to 2,166.36 kg, 1,822.59 to 2259.86 kg, 268.95 to 303.02 days, 6.62 to 7.93 kg/day, 10.64 to 14.09 kg, 38.67 to 51.68 days and 118.11 to 142.05 days, respectively in different parities up to sixth parity in Sahiwal cattle. Average age at first service was 26.46 months in Sahiwal cattle. Age at calving, number of services per conception, conception rate, gestation period, calving to first insemination interval, service period, calving interval and pregnancy rate ranged from 37.70 to 105.59 months (1,131–3,168 days), 1.84–2.02, 66.19–70.07%, 286.76–287.97 days, 72.65–87.61 days,113.48–150.48 days, 401.47– 443.47 days and 38–44%, respectively in different parities. The average longevity ranged from 7.43 to 11.35 years (2,711.95–4,142.75 days) in Sahiwal cattle up to sixth parity. In the present study, milk yield increased up to third parity and declined in further parities. Highest test day milk yield was recorded in second test day in each lactation up to sixth parity while lowest was observed in last test day.